2015
DOI: 10.1371/journal.pone.0123288
|View full text |Cite
|
Sign up to set email alerts
|

Codon Optimisation Is Key for Pernisine Expression in Escherichia coli

Abstract: BackgroundPernisine is an extracellular serine protease from the hyperthermophilic Archaeon Aeropyrum pernix K1. Low yields from the natural host and expression problems in heterologous hosts have limited the potential applications of pernisine in industry.Methodology/ Principal FindingsThe challenges of pernisine overexpression in Escherichia coli were overcome by codon preference optimisation and de-novo DNA synthesis. The following forms of the pernisine gene were cloned into the pMCSGx series of vectors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Multiple publications described heterologous protein yield increase after codon usage improvement. This is of particular interest for vaccine manufacturing process and industrial enzyme production as for example alpha‐amylase, pernisine, and prochymosine …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple publications described heterologous protein yield increase after codon usage improvement. This is of particular interest for vaccine manufacturing process and industrial enzyme production as for example alpha‐amylase, pernisine, and prochymosine …”
mentioning
confidence: 99%
“…of particular interest for vaccine manufacturing process [9] and industrial enzyme production as for example alpha-amylase, pernisine, and prochymosine [10][11][12] Rare codons generally correlate with lower levels of cognate tRNA and slower translation rates [13,14]. In some cases, their substitution has been shown to adversely affect the expression levels [15], solubility [16], cotranslational modifications [17] of encoded proteins, and to inhibit the functionality of specific proteins [18,19].…”
mentioning
confidence: 99%
“…The first method is codon optimization of the target gene. Codon optimization is a key step for the successful expression of protein in E. coli even from a distant host (Snajder et al 2015). Indeed, over the last decade, the use of codon-optimized genes in industrial biotechnology has reduced the cost of protein production, through improved protein expression (Elena et al 2014).…”
Section: Strategies For the Production Of Recombinant Protein (I) Optmentioning
confidence: 99%
“…It has been demonstrated that pernisine can efficiently degrade cellular and infectious bovine prion proteins [6], which today still present a challenge for decontamination processes, and this represents the main potential industrial application for pernisine. The protein sequence of fully unprocessed pernisine (i.e., prepropernisine) consists of 430 amino acids, which includes a putative signal sequence, as the first 24 amino acids, and a proposed proregion, from amino acids 25 to 92 [7, 8]. Pernisine is active at temperatures from 65 to 115 °C, and retains its catalytic activity across a wide pH range, from 4 to 10 [6].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, standard industrial fermentation facilities are not suitable for large-scale production of pernisine, due to its extreme cultivation conditions. Recombinant propernisine from Escherichia coli has similar properties to the wild-type enzyme, after an additional thermal activation step [7]. However, since the recombinant enzyme is located in the intracellular region or in the periplasm, additional downstream operations are required for its isolation and effective temperature pre-treatment.…”
Section: Introductionmentioning
confidence: 99%